Diagnostic Value of Typhidot and TUBEX-TF in Pediatric Typhoid Fever Using Composite Reference Standard - Salipadang, Eunike Jaequeline; Rauf, Syarifuddin; Pelupessy, Ninny Meutia; Rahimi, Rahmawaty; HK, Adhariana; Sarmila, Besse (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2025)
Typhoid fever, a systemic infection remains a significant global health concern, especially in endemic areas. Typhidot and TUBEX-TF present a quick, easy, and cost-effective, however, their diagnostic performance still needs to be evaluated. This study aims to evaluate Typhidot and TUBEX-TF diagnostic accuracy for typhoid fever in children using CRS composed of blood culture and PCR and recording its performance on fever days. This was a diagnostic study with a cross-sectional design involving children suspected of typhoid fever aged 1 to 18 years, in 7 hospitals in South Sulawesi, Indonesia from November 2023 to April 2024. Venous blood samples were collected from each respondent and tested using TUBEX-TF, Typhidot, and composite reference standard, a combination of blood culture and nested PCR, to improve diagnostic accuracy. Of 85 samples, 27 (31.8%) were positive for Typhidot, 14 (16.4%) for TUBEX-TF +4, and 44 (51.7%) for TUBEX-TF >+6. The positive rate for Typhidot dan TUBEX-TF >+6, was highest in the first week of fever (p<0.01). The sensitivity, specificity, PPV, and NPV (95% CI) of Typhidot were 43.55% (31.0-56.7), 100% (85.2-100), 100%, and 39.66%, respectively, and TUBEX-TF >+6 were 70.97% (58.1-81.8), 73.91% (51.6-89.8), 88%, and 48.57%, respectively. The combination of Typhidot and TUBEX-TF was also tested and resulted in higher diagnostic values (p=0.000). Therefore, combined Typhidot and TUBEX-TF testing is proposed as an effective strategy in the diagnosis of typhoid fever.